THE IMPERATIVE OF REGULATING BODY-WORN CAMERAS FOR THE INDONESIAN POLICE FORCE - Tantimin, Tantimin; Alhakim, Abdurrakhman (Masalah-Masalah Hukum, 2024)
Despite global adoption, Indonesia's criminal justice system lags in utilizing body-worn cameras (BWCs), hindered by the absence of a regulatory framework. This disparity complicates efforts to curb police misconduct, ensure accountability, and protect individual rights. The study underscores the urgency of promoting transparency and rebuilding public trust in law enforcement. It identifies a disconnect between the conceptual need for BWCs and the lack of normative support in Indonesia. Key challenges include oversimplified data classification, inadequate mechanisms for handling biometric data, and a lenient police code of ethics on evidence management. These issues pose significant challenges to the BWCs’ effectiveness, undermining their potential to enhance accountability. By addressing these issues, BWCs can realize their full potential in contributing to a more accountable and  ethical data protection standards.